Trends and Determinants of Female Genital Mutilation in Ethiopia: Multilevel Analysis of 2000, 2005 and 2016 Ethiopian Demographic and Health Surveys - Alemu, Addisu Alehegn (Int J Womens Health, 2021)
BACKGROUND: Female genital mutilation (FGM) is a harmful practice that causes health-related problems in the life of the affected women and girls. Though FGM is declared as a human right violation, studies revealed it is being practiced throughout Ethiopia. Therefore, this study was conducted to assess the prevalence, trends, and predictors of FGM among reproductive-aged (1549 years) women in Ethiopia. METHODS: Trends of FGM among reproductive-age women were estimated using the three Ethiopian Demographic and Health Survey (EDHS): 2000 (n=15,367), 2005 (n=14,070) and 2016 (n=7248) data. Multilevel logistic regression analysis was conducted to identify both individual- and community-level factors of FGM using the latest (2016) EDHS. To adjust potential confounders, the analysis was conducted considering sample weighting, clustering, and stratifications using STATA-14 software. RESULTS: The prevalence of FGM among women of reproductive age in Ethiopia decreased from 79.91% in 2000 to 70.37% in 2016. Similarly, FGM among daughters of circumcised mothers decreased from 56.16% in 2000 to 16.76% in 2016. Being Muslim (adjusted odds ratio [AOR] 5.48; 95% confidence interval [CI]: 4.23, 7.09), attending higher education (AOR 0.40; 95% CI: 0.29, 0.54), 45–49 years old (AOR 5.06; 95% CI: 3.38, 7.57), marriage at ≥ 18 years (AOR 0.80; 95% CI: 0.66, 0.96), not working (AOR 1.20; 95% CI: 1.02, 1.41), married (AOR 1.41; 95% CI: 1.12, 1.77) and residing in peripheral region (AOR 3.0.4; 95% CI: 1.96, 4.70) were determinants of FGM. CONCLUSION: Though the reduction of FGM among women of reproductive age in Ethiopia was minimal, it was encouraging among daughters of circumcised women over the last 16 years. Education, religion, age, age at marriage, occupation, marital status, and geographical regions were determinants of FGM. Combined and integrated interventions based on the identified factors are recommended to abandon FGM in Ethiopia.